Self Control Dan Penerimaan Orang Tua Terhadap Tingkat Kecemasan Orang Tua Pada Keberhasilan Pendidikan Anak Autis - Uswatun Hasanah (Universitas Islam Tribakti Lirboyo Kediri, 2017)
The purpose of this study is to obtain a picture of the extent to which self-control and acceptance of parents to the level of anxiety parents on the success of their children's education that bears autism. This study uses a qualitative approach. Characteristics of research subjects include parents who have children who are diagnosed with autism. The number of subjects in this study as many as 3 people. Technique of collecting data by interview as main method and observation as support method. The result of research indicate that overall the three subjects have good self-control and can fully accept the condition of their children who are diagnosed with autism and anxiety level on the success of their children's education with autism By the three subjects is very minimal. The acceptance is influenced by the support factors of the extended family, the family's financial capacity, religious background, education level, marital status, age and support of experts and the general public. Doctor's diagnosis, diet food, foster communication with doctor, psychologist, teacher and therapist, seek other doctors if the doctor is considered less cooperative, tell the truth when doing consultation about the development of his child enrich the knowledge, and accompany K when educating and therapy.